Factors Affecting The Success Rate Of The Covid-19 Vaccination Program In Silou Buttu Village, Pamatang Raya District, Simalungun Regency In 2022 - Masdalifah, Nur; Pasaribu, Riada M.; sihombing, Eka S.R; Silaban, Saroha Dame (Jurnal EduHealth, 2022)
The Corona Virus Disease pandemic is a health problem that is currently in the world's spotlight and has received attention from health scientists and the general public, where the government's handling process is carrying out the Covid-19 vaccination program. This study aims to determine the factors that influence the success rate of the Covid-19 vaccination program in Silou Buttu Village, Pamatang Raya District, Simalungun Regency by using a quantitative method with a Cross Sectional approach. The number of samples is 87 respondents. The results of the research from the data collected from the questionnaire with the Chi Square test showed that there was an effect of knowledge on the success rate of the Covid-19 vaccination program (P=0.011; α = 0.05), there was an effect between trust in the Covid-19 vaccine 19 with the success rate of the Covid-19 vaccination program (P=0.003; α = 0.05), there is an influence between the availability of the Covid-19 vaccine and the success rate of the Covid-19 vaccination program (P=0.002; α = 0.05), there is the influence between information and the success rate of the Covid-19 vaccination program (P=0.009; α = 0.05), there is an influence between the support of health workers and the success rate of the Covid-19 vaccination program. The conclusion is the influence of knowledge, trust in the Covid-19 vaccine, availability of the Covid-19 vaccine, information and support from health workers on the success rate of the Covid-19 vaccination program in Silou Buttu Village, Pamatang Raya District, Simalungun Regency. Suggestions to better understand and increase public awareness in carrying out the Covid-19 vaccination as a Covid-19 controller. The Corona Virus Disease pandemic is a health problem that is currently in the world's spotlight and has received attention from health scientists and the general public, where the government's handling process is carrying out the Covid-19 vaccination program. This study aims to determine the factors that influence the success rate of the Covid-19 vaccination program in Silou Buttu Village, Pamatang Raya District, Simalungun Regency by using a quantitative method with a Cross Sectional approach. The number of samples is 87 respondents. The results of the research from the data collected from the questionnaire with the Chi Square test showed that there was an effect of knowledge on the success rate of the Covid-19 vaccination program (P=0.011; α = 0.05), there was an effect between trust in the Covid-19 vaccine 19 with the success rate of the Covid-19 vaccination program (P=0.003; α = 0.05), there is an influence between the availability of the Covid-19 vaccine and the success rate of the Covid-19 vaccination program (P=0.002; α = 0.05), there is the influence between information and the success rate of the Covid-19 vaccination program (P=0.009; α = 0.05), there is an influence between the support of health workers and the success rate of the Covid-19 vaccination program. The conclusion is the influence of knowledge, trust in the Covid-19 vaccine, availability of the Covid-19 vaccine, information and support from health workers on the success rate of the Covid-19 vaccination program in Silou Buttu Village, Pamatang Raya District, Simalungun Regency. Suggestions to better understand and increase public awareness in carrying out the Covid-19 vaccination as a Covid-19 controller.